The contribution of income, social capital, and institutions to human well-being in Africa - Mina Baliamoune-Lutz; Stefan H. Lutz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
Using cross-sectional time series data from a large group of African countries, we examine the effects of income, institutions and social capital—with emphasis on the latter—on literacy and life expectancy. The empirical results confirm that income has a positive contribution. We also show that an improvement in institutions has positive influence on literacy but does not seem to affect life expectancy. Moreover, we find that the interaction between good institutions and high social capital produces a positive contribution to human well-being. This result suggests that social capital and institutions are complements, and underscores the important role of institutions.
Keywords: 330; Analphabetismus; Sterblichkeit; Lebensqualität; Einkommen; Social Capital; Institutionelle Infrastruktur